Analysis of vertical displacements of the esperanto footbridge in Bydgoszcz = Analiza przemieszczeń pionowych kładki esperanto w Bydgoszczy - Bujarkiewicz, Adam; Gajewski, Jarosław; Janiak, Tomasz; Sobczak-Piąstka, Justyna; Sztubecki, Jacek; Tews, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the research is a footbridge across the river Brda in Bydgoszcz. The measurements of the footbridge displacements with the test load were undertaken. The paper presents the results of the measurements and compares them with the theoretical results obtained using the finite element method (FEM).
Keywords: most wantowy; przemieszczenia; MES; cable-stayed bridges; displacements; FEM model